The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.10.18.22281194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immuno-epigenetic signature derived in saliva associates with the encephalopathy of prematurity and perinatal inflammatory disorders

Abstract: Background: Preterm birth is closely associated with a phenotype that includes brain dysmaturation and neurocognitive impairment, commonly termed Encephalopathy of Prematurity (EoP), of which systemic inflammation is considered a key driver. DNA methylation (DNAm) signatures of inflammation from peripheral blood associate with poor brain imaging outcomes in adult cohorts. However, the robustness of DNAm inflammatory scores in infancy, their relation to comorbidities of preterm birth characterised by inflammati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“…However, neither measure associated with all-cause mortality, which is in contrast with our study 10 . A seven-CpG score derived from an earlier EWAS by Ligthart et al has also been associated with a wide range of neurocognitive health outcomes in adults and neonates 7–9,4042 . These aggregate EWAS scores have shown promise in correlating with cardiometabolic disease risk and risk factors 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, neither measure associated with all-cause mortality, which is in contrast with our study 10 . A seven-CpG score derived from an earlier EWAS by Ligthart et al has also been associated with a wide range of neurocognitive health outcomes in adults and neonates 7–9,4042 . These aggregate EWAS scores have shown promise in correlating with cardiometabolic disease risk and risk factors 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…This is important to understand because early life immune dysregulation contributes to some neurodevelopmental disorders. For example, a recent study found that a DNAm-based proxy of CRP correlates with inflammation burden and MRI markers of encephalopathy of prematurity after preterm birth (39). Another limitation of this study is the lack of replication for MRI findings and the consideration of EpiScores from a single time-point.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we included EpiScores for growth and differentiation factor 15 (GDF15) and N-terminal-pro B-type natriuretic peptide (NTproBNP) [37], and CRP. The CRP EpiScore used was Barker et al ’s seven-CpG variation of Ligthart et al ’s CRP EpiScore [27,31], as this is known to correlate with birth GA, perinatal pro-inflammatory exposures, and neonatal brain development [32].…”
Section: Methodsmentioning
confidence: 99%
“…As well as having specific immunoregulatory roles, in the neonatal setting or relevant animal models, these proteins are associated with several comorbidities and developmental consequences of preterm birth. These include lung development and disease such as BPD [55][56][57][58][59][60][61][62][63][64][65][66][67], in utero and postnatal growth failure [68][69][70][71], HCA [7,72,73], patent ductus arteriosus [74][75][76][77], retinopathy of prematurity [78][79][80][81][82], NEC [83][84][85], hyperglycaemia [86], sepsis [85,[87][88][89][90], brain injury [32,[91][92][93][94], and neurodevelopmental outcomes [95][96][97][98]…”
Section: Associations Between Birth Ga and Episcoresmentioning
confidence: 99%
See 1 more Smart Citation